Prevalence of autoimmune diseases in patients with type 1 diabetes: a scoping review - Carlos Antonio Negrato; Rebecca Zerbinatti Pereira; Livia Domingos de Moraes Pimentel Porto; Ylana Walleska Santos Santana; Aline Kimmy Ikemoto Sato; Vitor Casoto de Melo; Miguel Luz Vilela Engel Vieira; Marilia de Brito Gomes (Einstein (São Paulo))
ABSTRACT Objective To evaluate the prevalence of autoimmune diseases in patients with type 1 diabetes mellitus. Methods This scoping review was conducted following the Joanna Briggs Institute guidelines and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) tool to ensure methodological rigor. We systematically searched PubMed, Embase, Scopus, Lilacs, and Web of Science databases to identify relevant literature published between 2018 and 2023. Results Twenty-four studies were included, mostly single-center studies from six continents, with varying study designs: 16 cross-sectional, seven retrospective, and one prospective cohort. The most prevalent autoimmune diseases found among patients with type 1 diabetes mellitus enrolled in these studies were autoimmune thyroiditis (5.5-41.2%), celiac disease (0.45-24.8%), rheumatoid arthritis (0.4-5.1%), and primary adrenal insufficiency (0.6-2.6%). Conclusion Autoimmune thyroiditis and celiac disease were the most prevalent autoimmune diseases in patients with type 1 diabetes mellitus. As the complexity of managing type 1 diabetes mellitus increases in the presence of multiple autoimmune comorbidities, further studies are required to elucidate the relationship between type 1 diabetes mellitus and different autoimmune pathologies. A deeper understanding of these associations will guide the development of public health policies, screening strategies, and educational initiatives tailored to the specific needs of this population.